The Use of Epifora in Modern Uzbek Poetry - Karimova Shakhnozakhon Karimovna (International Journal on Integrated Education, 2022)
It is well known that a number of forms of repetition are used in poetry. In particular, the epiphora, as an element of poetic syntax, serves to express certain meanings in poetry. The article discusses the relationship between “radif” and epiphora, and reveals the artistic functions of this type of repetition on the example of poems by poets such as Erkin Vahidov, Abdulla Aripov, Usmon Azim, Iqbol Mirzo.